TANTANGAN DAN SOLUSI: PENDIDIKAN, TEKNOLOGI, DAN MEDIA DALAM MENGHADAPI GLOBALISASI - Sisin Warini; Murdiana, Messy, Januar (Jurnal Komunikasi, 2024)
Education is a topic that is always interesting and current to discuss. The development of science and technology, which is marked by advances in the fields of information media and technology, is currently progressing so rapidly, that in placing a nation in a position, the extent to which the nation is advanced is based on how far the nation has mastered these two fields. The method used is the library research method. The aim of this research is to discuss problems in the world of education, to find out developments in technology and media, and ways of education in facing the challenges of globalization. The results of this research are: First, problems at the input stage. Second, problems with the process. Third, problems with output. Education in facing the challenges of globalization: education must be able to produce quality human resources, know science and technology and improve quality